Improving disciplinary proceeding in enhancing good governance in the public sector / Ahmad Martadha Mohamed...[et al.] - Mohamed, Ahmad Martadha; Sakdan, Mohd Foad; John Abdullah, Siti Alida; Ahmad, Rusniah; Khalil, Samihah; Muslim, Sakinah; Dollah, Noor Faizzah; Akmal Ismail, Nur Syakiran (2010)
Public service is fundamental to good governance. It is an integral part of democracy because it serves as the neutral administrative structure which carries out the decisions of elected representatives of the people. With the advent of the modern state, government officials have been and are seen as stewards of public resources and guardians of a special trust that citizens have placed in them. In return for this confidence, they are expected to put public interest above self-interest. As such, public officials should have higher standards of performance and conduct than others. Yet, this is too realistic. Therefore there must be disciplinary mechanism. The objective of disciplinary action is to change the behavior of the individual concerned and to show other workers that discipline will not be tolerated. However, implementing an effective disciplinary system is one of the most difficult tasks. This paper, therefore, attempts to highlight the importance of disciplinary proceeding as an important control mechanism to enhance and strengthen the quality of good governance among public employees. In doing so, the authors argue that progressive discipline should replace the traditional punitive types of disciplinary action to handle disciplinary cases. This is because progressive discipline is based on the premise that discipline ought to have a positive rather than punitive focus.